Benign Recurrent Vertigo: The Course of Vertigo Attacks Compared to Patients With Menière's Disease and Vestibular Migraine - van Leeuwen, Roeland B.; Colijn, Carla; van Esch, Babette F.; Schermer, Tjard R. (Frontiers in Neurology, 2022)
Objective – To explore the course of vertigo attacks in patients with benign recurrent vertigo (BRV) as compared to patients with Menière’s disease (MD) and vestibular migraine (VM). Study design – Prospective cohort study. Setting – Tertiary referral center. Patients – Adult patients who visited the Apeldoorn Dizziness Centre between January 2015 and November 2016 and who were diagnosed with BRV, VM or MD. During three years participants were contacted every six months by telephone to complete a study-specific questionnaire. Main outcome measures – Vertigo attack frequency, use of medication, and Hospital Anxiety and Depression Scale (HADS). Results – The study population (n=121) consisted of 44 patients with BRV, 34 with VM, and 43 with MD. For the total follow-up period no statistically significant differences between the three diagnosis groups were observed for being attack-free in the past six months: OR=0.86 (95%CI 0.34 to 2.17; p=0.745) for VM and OR=1.06 (95%CI 0.44 to 2.51; p=0.902) for MD, compared to BRV. Overall, 19 patients (43.2%) with BRV, 13 (38.2%) with VM, and 35 (81.0%) with MD used medication to prevent vertigo attacks at any point during their three-year follow-up. Throughout the observation period patients with MD showed an average of 3.37 points (95%CI 0.68 to 6.07; p=0.014) higher HADS scores relative to patients with BRV. Conclusion - The course of vertigo attacks was rather favorable in the three groups: after three years of follow-up, as 67 to 70 percent of the patients were free of vertigo attacks. The course of disease in patients with BRV was not distinctive from patients with MD and VM. We assume that BRV is a mild or incomplete variant of VM and MD, rather than a separate disease entity with distinct pathognomonic features.